Translingual Practice. - Canagarajah, A. Suresh (Taylor and Francis, 2012)
Translingual Practice: Global Englishes and Cosmopolitan Relations introduces a new way of looking at the use of English within a global context. Challenging traditional approaches in second language acquisition and English language teaching, this book incorporates recent advances in multilingual studies, sociolinguistics, and new literacy studies to articulate a new perspective on this area. Canagarajah argues that multilinguals merge their own languages and values into English, which opens up various negotiation strategies that help them decode other unique varieties of English a.